Study of the Chromosomal Abnormalities and Associated Complex Karyotypes in Hematological Cancer in the Population of West Bengal: A Prospective Observational Study - De, Puspal; Mukhopadhyay, Madhumitha J (Indian Journal of Medical and Paediatric Oncology, 2021)
Introduction Chromosomal instability is an important feature of hematological cancer. The pathogenesis is complex and it involves genetic and epigenetic factors. As a genetic factor, chromosomal instability may play a key role in leukemogenesis. Accumulation of genetic alteration is mainly responsible for numerical and structural chromosomal rearrangement or clonal evaluation. But disease progression is often driven by chromosomal translocation, hyper- or hypodiploidy with structural abnormalities, and complex karyotypes.Objective This research aimed to study the different types of chromosomal abnormalities in clinically suspected hematological cancer patients.Materials and Methods Cytogenetic analysis was performed based on phytohemaglutinin stimulated peripheral blood lymphocyte cultures and bone marrow culture, without mitogen, of the respective patients of West Bengal from March 2016 to February 2018. All clinically suspected hematological cancer patients referred for karyotyping to the institutional genetics department have been included without any biasness of sex and age. Karyotypes were described according to the International System for Cytogenetic Nomenclature (ISCN 2005).Results In the present study, 56 clinically suspected hematological cancer cases were observed and 41 cases of chromosomal rearrangement were found which clearly show chromosomal instability as the main driving force for hematological cancer transformation. Presence of variant Philadelphia chromosomes with classical translocation, mosaic complex karyotypes, variable numerical, and structural chromosomal abnormality, along with severe-to-moderate hypo- and hyperdiploidy, and presence of marker chromosomes were the main findings of this study.Conclusion The result shows that the detection of chromosomal instability was important for preliminary diagnosis, treatment, prognosis, and further management. So the present study provided additional information about chromosomal instability in hematological cancer at Kolkata and adjoining regions.
Keywords: chromosomal instability; hematological cancer; complex karyotype; leukocyte culture